Hydrogenation of zirconium film by implantation of hydrogen ions - 刘洋 方开洪 吕会议 刘际伟 王博宇 (Plasma science & technology, 2017)
In order to understand the dnve-in target in a D-D type neutron generator,it is essential to study the mechanism of the interaction between hydrogen ion beams and the hydrogenabsorbing metal film.The present research concerns the nucleation of hydride within zirconium film implanted with hydrogen ions.Doses of 30 keV hydrogen ions ranging from 4.30×10~（17） to1.43×10~（18） ions cm~（-2） were loaded into the zirconium film through the ion beam implantation technique.Features of the surface morphology and transformation of phase structures were investigated with scanning electron microscopy,atomic force microscopy and x-ray diffraction.Confirmation of the formation of 5 phase zirconium hydride in the implanted samples was first made by x-ray diffraction,and the different stages in the gradual nucleation and growth of zirconium hydride were then observed by atomic force microscope and scanning electron microscopy.